LEGAL STATUS OF STATE PERSONNEL UNDER OUTSOURCING CONTRACT : STUDY ON BENEFITS AND WELFARE PROTECTION - รูปสูง, มณฑินี (Huachiew Chalermprakiet Law Journal, 2020)
This article studies strongly about the problem regarding the legal status of the state personnel under outsourcing contract by researching the benefit and the welfare protection of such people for the purpose of seeking answer to the question “ whether the legal status of the outsourcing contractor that is the natural person and the state parties is the state personnel or not ” and “ should the outsourcing contractor’s benefit and welfare be protected or not, if it should be protected according to which law.” because It is evident in the fact that the outsourcing contractor in the state sector actually has a legal relation with the state through the employment contract and whose legal status is a sort of “state employee” existing in the Thai law system. However, due to the fact that presently the state personnel which has the legal status as a state employee in Thai law system is not only exist in one type especially in the government sector, there are two types of the personnel under such status; government employees and temporary employees, which besides the same legal status, the job description is alike too. Therefore, the latter issue is about the question concerning the categorizing of the state personnel in Thai law system. In consequence, this article also seeks to search for the guideline for the government organization to apply the discretion on how to adopt the legal relation form of the state personnel.